A digital watermarking for anaglyph 3D images - Zadokar, Sanjay R.; Raskar, Vishal B.; Shinde, Sachin V. (ICACCI : 2013 International Conference on Advances in Computing, Communications and Informatics : 22-25 August 2013, 2013)
In today's world, development in various field is attracting people for enhancing the technology. As a result of this scenario, now people are able to experience a 3D view of an image by using a combination of electronics & signal processing. The exposure of 3D technology is now way booming and the people show the enormous interest on 3D technology because it provides an immersive experience to the viewers. As 3D devices are being available, data hiding techniques for 3D images is also being implemented now. The depth image based rendering (DIBR) 3D image is one of the image based 3D data which consists of the center image and depth image, anaglyph 3D image being one of the type of centre image which is composed of left eye image, right eye image and the depth image. Watermarking i.e. content protection is done with the help of discrete wavelet transform (DWT) on anaglyph 3D images. To increase robustness of the proposed system, selection of row coefficient is necessary therefore we select certain coefficient sub blocks and group the coefficients rows based on properties of DIBR. The simulation shows that the stable extraction of embedded watermark is done from the synthesized anaglyph centre 3D image and depth image. The embedded watermark can be efficiently extracted despite any noise attack on a front image. The proposed scheme is applicable for any compression technique as well as on any type of image.